Pengelolaan Desa Wisata Berbasis Community Based-Tourism di Desa Adat Osing Kemiren, Kabupaten Banyuwangi - Fitriyah Umar, Lathifatul; Sjamsuddin, Sjamsiar; Rochmah, Siti (Jurnal Ilmiah Administrasi Publik, 2023)
The management of the Osing Kemiren Traditional Tourism Village implements a Community Based-Tourism system which aims to provide the widest opportunity for communities to explore and develop their potential, but the management is still not optimal because there are still many people who are not aware of the tourism potential that they have. This study aims to explain the management of village tourism based on Community Based-Tourism in the Osing Kemiren Traditional Village and its challenge. The type of research is qualitative. The results of the study, there is community participation in the management of tourism village. Then, the environment is better maintained due to the development of tourist villages. There is cultural preservation which is also implemented. Income distribution from the results of tourism activities is also applied. The conclusion is community-based tourism is good, but in terms of the principle of income distribution, can be  developed. Income distribution for the community in managing tourism in the Osing Kemiren Traditional Village based on their role in tourism activities.